The Influence of Service Quality and Service Experience on Word of Mouth (WOM ) Through Perceived Value of Tour Travel Congregants in Malang City - Karimatun Nisa, Farida; Khodir Djaelani, Abdul; Susyanti, Jeni (LP2M IAIN Palopo, 2025)
This study aims to analyze the influence of service, quality, and service experience on word of mouth (WOM) through perceived value on tour travel pilgrims in Malang City. This type of research is a quantitative approach research. The results of the calculation are 100 samples of Cooper and Emory. This study uses the Moderated Regression Analysis (MRA) model and Structural Equation Model (SME) analysis based on Partial Least Square (PLS) with the help of SmartPLS version 3.0. The results of the study show that the service quality variable has a significant and positive influence on word of mouth on tour travel pilgrims in Malang City. The service experience variable does not have a significant influence on word of mouth on tour travel pilgrims in Malang City. The service quality variable has a significant and positive influence on received value on tour travel pilgrims in Malang City. The service experience variable has a significant and positive influence on received value on tour travel pilgrims in Malang City. The received value variable has a significant and positive influence on word of mouth among tour travel pilgrims in Malang city. The received value variable can mediate the relationship between service quality and word of mouth with a positive and significant influence on word of mouth. The received value variable can mediate the relationship between service experience and word of mouth with a positive and significant influence on word of mouth.